STUDENTS’ PERCEPTION OF THE USE OF ISLAMIC ENGLISH SONGS IN LEARNING LISTENING AT MADRASAH ALIYAH OF PESANTREN MODERN IMMIM PUTRA MAKASSAR - Mahdi H, Muh. Firas; Talib, Ahmad; Baa, Sultan (Universitas Negeri Makassar, 2022)
The objective of this study was to find out students’ perception of the use of Islamic English songs in learning and listening at Madrasah Aliyah of Pesantren Modern IMMIM Putra Makassar. This research used the mixed methods approach. The population of this research was the students of the third-grade Madrasah Aliyah of Pesantren Modern IMMIM Putra Makassar. Through a purposive sampling technique, there were 21 students in the third grade were chosen to be the sample of this research. The instruments of this research were a questionnaire and an interview. The research findings showed that there are 8 students (38.1%) in the category of strongly positive perception, and 7 students (33.3%) in the category of positive perception. It is supported by the data obtained based on the three aspects of perception. From the cognitive aspect, 8 students (38.1%) were in the strongly positive category and 8 students (38.1%) were in the positive category. From the affective aspect, 8 students (38.1%) were in the strongly positive category and 8 students (38.1%) were in the positive category. From the conative aspect, 10 students (47.62%) were in the strongly positive category and 6 students (28.57%) were in the positive category. The researcher also found some additional information from the interview results. It was found that the students “agreed to”, “were comfortable about”, and “were motivated to” the use of Islamic English songs in learning listening at Madrasah Aliyah of Pesantren Modern IMMIM Putra Makassar.